Faktor-Faktor Yang Berhubungan Dengan Keikutsertaan Ibu Hamil Dalam Program Vaksinasi COVID-19 - Noviani Karnita; Novelia Shinta; Rukmaini Rukmaini (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
Pregnant women are at high risk of being infected with COVID-19 which will increase the risk of death for both mother and baby. Currently, data regarding the participation of pregnant women in the COVID-19 vaccination program is still far from the target, due to many influencing factors such as age, education, knowledge, family support, and community culture. This study aims to analyze the factors that influence the participation of pregnant women in the COVID-19 vaccination program in the East Belitung Regency. The type of research used is quantitative research with a Cross Sectional approach. The sample size in this study was 100 pregnant women respondents in the East Belitung Regency. The observed variable is the independent variable (age, education, knowledge, family support, and community culture) which will be associated with the dependent variable (covid-19 vaccination participation) with the chi-square test. The results of this study prove that there is a significant relationship between age (p-value = 0.000), education (p-value = 0.000), knowledge (p-value = 0.000), family support (p-value = 0.000), and community culture (p-value = 0.000) with the participation of pregnant women in the COVID-19 vaccination program in the East Belitung Regency Region.